THE ROLE OF COMMUNITY COMPLAINTS POSTS IN SETTLEMENT OF ALLEGED CASES OF ENVIRONMENTAL DAMAGE AND POLLUTION - Nanda Melani; Ninne Zahara Silviani (ConCEPt - Conference on Community Engagement Project, 2022)
The number of cases of environmental damage and pollution that occurred in Batam has made the Environmental Service (Dinas Lingkungan Hidup/DLH) create a complaint station a forum for the public to be able to report all allegations related to the occurrence of environmental pollution and/or damage. The increasing number of cases of environmental damage and pollution is indicated by the increasing number of complaints reported by the public to the agency and the many obstacles faced by the community. The purpose of this activity, among others, is to find out the requirements for public complaints and provide information about the flow of complaints handling carried out by the DLH Batam City so that the information obtained is accurate enough to make the public more sensitive to the surrounding environment to report any pollution actions. The implementation method in carrying out PKM activities passes through several stages. At the initial stage, PKM preparations were carried out to the relevant agencies. The next stage will be observation and identification of the subject matter and carry out data collection which will be analyzed at the Batam City Environmental Service. The author makes a project output design based on practical workplace conditions. At the last stage the author makes a PKM report. The results of this PKM show information regarding the complain station in the settlement of alleged cases of environmental damage and pollution based on the Regulation of the Minister of the Environment Number 22 of 2017 concerning procedures for managing complaints of alleged environmental pollution/damage and destruction. Forest. The output of the project made by the author is a stage that takes place at the PKM location